-7+x=13x the -7=12x and x =-7/12
7=x+1 6=x
3x + 7 = -4x + 28 implies 7x + 7 = 28
Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7
If x=4 then 2x+7 =
9 plus 7 equals 144. Generally, x plus y = x(x+y).
-7+x=13x the -7=12x and x =-7/12
7=x+1 6=x
3x + 7 = -4x + 28 implies 7x + 7 = 28
Can you help with this equation? Thanks. Solve for x and y and z for the following. x plus y plus z equals 9 x plus 2y plus 3z equals 23 x plus 5y plus -3z equals -7
If x=4 then 2x+7 =
5+5x5=30 but (5+5)x5=50
7
7(9+x) myalgebra.com
x = 7
(3, 5)
7